Concreteness fading in learning secondary school physics concepts. (February 2022) - Kokkonen, Tommi; Lichtenberger, Andreas; Schalk, Lennart
Abstract: Concreteness fading has been proposed as a general instructional approach to support learning of abstract mathematics and science concepts. Accordingly, organizing external knowledge representations in a three-step concrete-to-idealized sequence should be more beneficial than the reverse, concreteness introduction, sequence. So far, evidence for the benefits of concreteness fading come mainly from studies investigating learning of basic mathematics concepts. Studies on learning natural science concepts are scarce and have not implemented the full three-step-sequence. In an experimental classroom study ( N = 70), we compared concreteness fading and concreteness introduction in high school science education about electromagnetic induction using a detailed assessment. Furthermore, we explored whether these sequences differentially affect the use of the different representations during instruction. Both sequences were equally effective and there were no differences in using the representations. We discuss why our results question the proposed advantages of concreteness fading and highlight conceptual differences and learning goals across domains. Highlights: Concreteness fading (CF) and concreteness introduction (CI) were compared. Equivalence tests indicate similar performance from CF and CI for learning physics. These results question the generality of concreteness fading.